Travel & See : Black Diaspora Art Practices since the 1980s - Mercer, Kobena, 1960- (Book collections on Project MUSE., 2016)
"Over the years, Kobena Mercer has critically illuminated the visual innovations of African American and black British artists. In Travel & See he presents a diasporic model of criticism that gives close attention to aesthetic strategies while tracing the shifting political and cultural contexts in which black visual art circulates. In eighteen essays, which cover the period from 1992 to 2012 and discuss such leading artists as Isaac Julien, Renee Green, Kerry James Marshall, and Yinka Shonibare, Mercer provides nothing less than a counternarrative of global contemporary art that reveals how the "dialogical principle" of cross-cultural interaction not only has transformed commonplace perceptions of blackness today but challenges us to rethink the entangled history of modernism as well"--Back cover.